Fabrication of CuAlVMg High-Temperature Shape Memory Alloy Containing Low-Soluble Vanadium Addition - Karaduman, Oktay; Boyrazli, Mustafa; Canbay, Canan Aksu; Ozkul, Iskender; Celik, Emrah; Basbag, Gunes (Springer India, 2024)
For the first time, CuAlVMg high-temperature shape memory alloy (HTSMA) with unprecedented alloy composition and with extended solubility of vanadium element was fabricated as-cast ingot by arc melting method, then homogenization of the alloy in high beta-phase temperature region and quenching in iced-brine water were performed, respectively. The characteristic forward martensite to austenite martensitic transformation (MT) temperatures were detected at around 390 degrees C, which put the novel alloy in the category of HTSMAs. The thermal response of the alloy at high-temperatures was observed by DTA test as coherent with usual Cu-based HTSMAs. The residual sub-eutectoid precipitations emerging at around 500 degrees C hindered the direct martensitic transformation. The martensite structure of the alloy was revealed by XRD, SEM and optical microscopy tests.
Keywords: CuAlVMg HTSMA; Shape memory effect; Low-soluble vanadium; DSC; DTA; Martensitic transformation; Crystallite size